Clinical psychology : an introduction - Carr, Alan, 1957- (New York : Routledge, 2012)
"Clinical psychology: An Introduction is for students studying clinical psychology as part of an undergraduate programme in psychology, nursing, sociology or social and behavioural sciences. Undergraduate students who wish to know if postgraduate study in clinical psychology would be of interest to them will find this book particularly useful. The book will inform students about - the profession of clinical psychology - how to get onto a clinical psychology postgraduate training programme - the way clinical psychologists work with children, adolescents and adults with common psychological problems - the main models of practice used by clinical psychologists, and - the scientific evidence for the effectiveness of psychological interventions. There is a focus on both clinical case studies and relevant research, and the book includes chapter plans, summaries, revision questions, advice on further reading and glossaries of key terms, all of which make it a brief student-friendly introduction to an exceptionally interesting subject"--
Includes bibliographical references and index.
Keywords: Clinical psychology -- Textbooks; PSYCHOLOGY / Clinical Psychology; PSYCHOLOGY / Mental Health